Altered β-adrenoceptor function associated to protein kinase C activation in hyperproliferative T lymphocytes - Cremaschi, Graciela Alicia (2000)
β-Adrenoceptor (βAR) expression and function as well as its modulation via intracellular transduction signals, were analyzed on the T cell lymphoma BW5147. Independently to the kinetic of proliferation and relative to the number of receptors displayed in normal T lymphocytes, BW5147 cells displayed a decreased number of βAR, uncoupled to adenylate cyclase, but coupled to protein kinase C stimulation. This last effect was impaired by a β- antagonist and by blockers of the enzymatic pathways involved in T lymphocyte proliferation, inducing a recovery of βAR sites. Down-regulation of βAR would implicate the loss of a negative neuroimmune control mechanism for lymphocyte proliferation. The coupling of the remaining sites to a positive signal for cellular activation, would contribute to establish an hyperproliferative state. (C) 2000 Elsevier Science B.V.